Drug-Coated Balloon Versus Standard Balloon for Superficial Femoral Artery In-Stent Restenosis: The Randomized Femoral Artery In-Stent Restenosis (FAIR) Trial. Issue 23 (8th December 2015) - Krankenberg, Hans; Tübler, Thilo; Ingwersen, Maja; Schlüter, Michael; Scheinert, Dierk; Blessing, Erwin; Sixt, Sebastian; Kieback, Arne; Beschorner, Ulrich; Zeller, Thomas
Abstract : Background—: Drug-coated balloon angioplasty (DCBA) was shown to be superior to standard balloon angioplasty (POBA) in terms of restenosis prevention for de novo superficial femoral artery disease. For in-stent restenosis, the benefit of DCBA over POBA remains uncertain. Methods and Results—: One hundred nineteen patients with superficial femoral artery in-stent restenosis and chronic limb ischemia were recruited over 34 months at 5 German clinical sites and prospectively randomized to either DCBA (n=62) or POBA (n=57). Mean lesion length was 82.2±68.4 mm. Thirty-four (28.6%) lesions were totally occluded; 30 (25.2%) were moderately or heavily calcified. Clinical and duplex ultrasound follow-up was conducted at 6 and 12 months. The primary end point of recurrent in-stent restenosis assessed by ultrasound at 6 months was 15.4% (8 of 52) in the DCBA and 44.7% (21 of 47) in the POBA group ( P =0.002). Freedom from target lesion revascularization was 96.4% versus 81.0% ( P =0.0117) at 6 months and 90.8% versus 52.6% ( P <0.0001) at 12 months, respectively. At 12 months, clinical improvement by ≥1 Rutherford category without the need for target lesion revascularization was observed in 35 of 45 DCBA patients (77.8%) and 23 of 44 POBA patients (52.3%; P =0.015). No major amputation was needed. Two patients in the DCBA and 3 patients in the POBA group died. No death was procedure related. Conclusions—: DCBA for superficial femoral artery in-stent restenosis is associated with less recurrent restenosis and a better clinical outcome than POBA without an apparent difference in safety. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01305070.